Inhame (Dioscorea cayennensis) cultivado na Paraíba: caracterização e produção de concentrado proteico para prospecção de peptídeos bioativos obtidos através de digestão simulada in vitro - Nascimento, Edilza Silva do (2020)
The yam is an important tuber in Brazil Northeast food culture, also being considered a functional food, as it has proteins with potential bioactive properties. The objective of this study was to characterize the peptide profile and perform the bioprospection of bioactive peptides obtained from in vitro simulated gastrointestinal digestion of yam proteins (Dioscorea cayennensis) grown in Brazil. Therefore, the sample obtained was initially analyzed for partial chemical composition, followed by obtaining the flour for the yam extract and protein concentrate (YPC) preparation, submitted to simulated digestion in vitro, and finally the characterization and profile of the obtained peptides were performed. The protein extract was subjected to isoelectric precipitation to obtain the YPC, which was then dialyzed and freeze-dried. The YPC was submitted to simulated gastrointestinal (GI) digestion, generating two phases: the gastric phase hydrolysate (GPH) and continuous hydrolysis until the gastrointestinal phase hydrolysate (GIPH). The samples: YPC, GPH and GIPH were submitted to analysis of protein and peptide profile: total amino acids and free amino acids (FAA); molecular mass (MM); hydrophobicity by reverse phase chromatography and electrophoresis (Tricine-SDS-PAGE); protein profile (two-dimensional gel electrophoresis) and peptide profile (nano-LC-ESI-MS/MS, MALDI-TOF). The identified peptides were submitted to the bioactivity prediction through the Bioactive Peptides Database (BIOPEP) and PeptideRanker (inhibitory activity of the angiotensin-converting enzyme-ACE). To validate results obtained in silico, analysis were performed to determine biological activities in vitro: antioxidant (DPPH, ABTS, ORAC and protection from DNA damage), antibacterial and ACE’s inhibitor. The results of 2D-electrophoresis show the presence of the dioscorin protein, as the yam’s major protein. The YCP resulted in 64.0 % protein, with all essential amino acids with an appropriate score according to FAO, except sulfur amino acids. After the GI digestion of the YPC, a significant increase in the release (p <0.5) of AAL was evidenced. The efficiency of GI digestion was verified according to the distribution profile of MW, with approximately 71.0 % of peptides with MW <2 kDa generated in the GIPH. Most of the identified peptides belong to the D. cayennensis dioscorin protein. GPH peptides had their MM decreased with the progression of GI hydrolysis, resulting in smaller MM peptides in GIPH. In addition, sequences with potential for bioactive peptides, with antihypertensive, antidiabetic, antioxidant and antibacterial activity were identified from the BIOPEP prediction. The presence of a peptide sequence containing proline and leucine (LAPLPL) was found in the GPH and GIPH, which can contribute to the inhibition of ACE, as well as peptides containing aromatic residues in the C-terminal (DITWT and FLSWT) that allow the donation of electrons and stabilization of free radicals. These findings suggest that these characteristics contributed to the antioxidant activity in all in vitro assays. Hydrophobic and positively charged peptides (IFDQTLGKLR) may have made it possible to inhibit the growth of the bacteria Escherichia coli. Therefore, the peptides obtained after the GI digestion of yam proteins can contribute to the prevention of infections and chronic degenerative diseases development, with an impact on human health.